2021
DOI: 10.1101/2021.04.12.439521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of Mpv17 on hair-cell mitochondrial homeostasis, synapse integrity, and vulnerability to damage in the zebrafish lateral line

Abstract: Noise exposure is particularly stressful to hair-cell mitochondria, which must produce enough energy to meet high metabolic demands as well as regulate local intracellular Ca2+ concentrations. Mitochondrial Inner Membrane Protein 17 (Mpv17) functions as a non-selective channel and plays a role in maintaining mitochondrial homeostasis. In zebrafish, hair cells in mpv17a9/a9 mutants displayed elevated levels of reactive oxygen species (ROS), elevated mitochondrial calcium, hyperpolarized transmembrane potential,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Numerous studies have indicated that dexamethasone can induce mitochondrial dysfunction in various tissues, including adipocytes (Luan et al, 2019), skeletal muscle (Liu et al, 2016), and neurons (Du et al, 2009). We previously reported reduced hair cell uptake of the cationic dye FM1-43 in zebrafish mutants with impaired hair cell mitochondrial function ( mpv17 -/- ), indicating that these fish possessed reduced driving force for cations through mechanotransduction channels, and elevated hair cell mitochondrial calcium (Holmgren & Sheets, 2021). We therefore evaluated whether 48-hour dexamethasone exposure affected hair cell uptake of FM1-43 and calcium homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that dexamethasone can induce mitochondrial dysfunction in various tissues, including adipocytes (Luan et al, 2019), skeletal muscle (Liu et al, 2016), and neurons (Du et al, 2009). We previously reported reduced hair cell uptake of the cationic dye FM1-43 in zebrafish mutants with impaired hair cell mitochondrial function ( mpv17 -/- ), indicating that these fish possessed reduced driving force for cations through mechanotransduction channels, and elevated hair cell mitochondrial calcium (Holmgren & Sheets, 2021). We therefore evaluated whether 48-hour dexamethasone exposure affected hair cell uptake of FM1-43 and calcium homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated TMRE fluorescence was apparent not only in the mitochondria of hair cells (Fig 8 A’, B’, F; EGFP-negative cells), but also the surrounding supporting cells (Fig 8 A”, B”, G; EGFP-positive cells), suggesting prolonged dexamethasone exposure disrupts normal mitochondrial function in both hair cells and supporting cells. Given that the hair cells in dexamethasone-treated larvae had more negatively charged ΔΨm, we predicted that these hair cells would be more vulnerable to neomycin-induced hair cell death (Alassaf et al, 2019; Holmgren & Sheets, 2021). When treated with higher doses of neomycin (50-100 μM), we observed significantly more lateral-line hair cell loss in fish pre-exposed for 48 hours to dexamethasone, relative to controls (Fig 9 K; adjusted P= 0.1407 (30 μM), *P=0.0353 (50 μM), ****P<0.0001 (100 μM)).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have indicated that dexamethasone can induce mitochondrial dysfunction in various tissues, including adipocytes [32], skeletal muscle [33], and neurons [34]. We previously reported reduced hair cell uptake of the cationic dye FM1-43 in zebrafish mutants with impaired hair cell mitochondrial function (mpv17 −/− ), indicating that these fish possessed reduced driving force for cations through mechanotransduction channels, and elevated hair cell mitochondrial calcium [35]. We therefore evaluated A, B) and neomycin injured neuromasts (C-F).…”
Section: Hair Cell Fm1-43 Uptake and Calcium Homeostasis Is Unaffecte...mentioning
confidence: 99%
“…8A″, B″, E; EGFP-positive cells), suggesting prolonged dexamethasone exposure disrupts normal mitochondrial function in both hair cells and supporting cells. Given that the hair cells in dexamethasone-treated larvae had more negatively charged ΔΨm, we predicted that these hair cells would be more vulnerable to neomycin-induced hair cell death [35,37]. We therefore compared neomycin-induced hair cell lesion in fish pre-treated with dexamethasone or DMSO carrier alone (Fig.…”
Section: Prolonged Dexamethasone Exposure Hyperpolarizes Neuromast Mi...mentioning
confidence: 99%